2002
DOI: 10.1038/sj.bmt.1703674
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated donor BMT recipients given pretransplant low-dose antithymocyte globulin have outcomes equivalent to matched sibling BMT: a matched pair analysis

Abstract: Summary:Fifty-seven patients receiving unrelated donor (UD) BMT were matched for disease and stage with 57 recipients of genotypically matched related donor (MRD) BMT. All UD recipients were matched serologically for A and B and by high resolution for DR and DQ antigens. All patients received CsA and 'short course' methotrexate with folinic acid. Unrelated donor BMT patients also received thymoglobulin 4.5 mg/kg (6 mg/kg if Ͻ30 kg) in divided doses over 3 days pretransplant. For UD and RD BMT, respectively, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 13 publications
2
50
1
Order By: Relevance
“…TG was applied in divided doses with a last dose given on day -1 or even on day 0 in matched related and unrelated transplantation and resulted in a rate of acute GVHD grades II-IV of about 20%. 20,21 In conclusion, reduced-intensity conditioning with BU/ FLU in HLA-identical sibling transplants led to faster platelet engraftment and less transfusion support compared to conditioning with BU/FLU/ATG. Administration of ATG did not influence the rate of graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…TG was applied in divided doses with a last dose given on day -1 or even on day 0 in matched related and unrelated transplantation and resulted in a rate of acute GVHD grades II-IV of about 20%. 20,21 In conclusion, reduced-intensity conditioning with BU/ FLU in HLA-identical sibling transplants led to faster platelet engraftment and less transfusion support compared to conditioning with BU/FLU/ATG. Administration of ATG did not influence the rate of graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The Alberta group in Canada has gone further still, and has completed a matched pair analysis of MUD transplants receiving ATG in the conditioning regimen, with HLAidentical sibling transplants not receiving ATG. 26 In this study, all patients received the FLUBUP regimen (fludarabine, intravenous busulfan, peripheral blood allogeneic stem cells). Acute GvHD grade II was 19 vs 36% for patients receiving or not ATG, grade III-IV was 10 vs 18%.…”
Section: Comparative Nonrandomized Studiesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] One of these 23 23 Recently, the German cooperative group studied 155 patients with acute myeloid leukemia (AML) undergoing an allogeneic UD transplant: 87 received ATG as part of the conditioning regimen, whereas 68 did not. Grade III-IV acute GvHD was seen in 12% of the ATG patients vs 22% of the non-ATG patients (P ¼ 0.04) 24 (Table 1).…”
Section: Comparative Nonrandomized Studiesmentioning
confidence: 99%
“…2 Several previous studies have suggested suitable doses of ATG in matched unrelated transplantations. 3,4 However, to date, the optimal dose of ATG with respect to the prevention of severe GVHD following the haploidentical transplantation is unknown.…”
Section: Introductionmentioning
confidence: 99%